Analisis Efisiensi Exhaust Gas Auxiliary Engine Kapal Motor dengan Perhitungan Heat Loss - Yudhi Chandra Dwiaji; Sinthya Prahasti Nidyasari (Politeknosains, 2018)
In a ship generally has 2 types of engines, namely the Main Engine (ME) as the driving force of the ship and the Auxiliary Engine (AE) as a supplier of electricity from the power generated by ME. At present the Amrta Jaya 1 Ship utilizes the ME exhaust gas to heat the boiler economizer. Unfortunately this is considered less efficient because the distance is too far between ME and economizer so it takes longer when OHN (one hour notice). To overcome the conventional method, the research was carried out by utilizing the AE exhaust gas which has a distance closer to the economizer. Calculations to determine the heat loss that occurs from the exhaust gas AE to economizer through a copper nickel pipe with a diameter of 1 inch and an insulation thickness of 2 cm, obtained heat loss of 10,539 Watts where the value is still below the maximum heat loss piping system assumed to be 923.52 Watts. So that by utilizing this auxiliary engine exhaust gas, it can be carried out a cost savings of around Rp. 7,875,000.00 when the ship performs an OHN.